If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7x + 1x = 6x + 3 + 5x Combine like terms: 7x + 1x = 8x 8x = 6x + 3 + 5x Reorder the terms: 8x = 3 + 6x + 5x Combine like terms: 6x + 5x = 11x 8x = 3 + 11x Solving 8x = 3 + 11x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-11x' to each side of the equation. 8x + -11x = 3 + 11x + -11x Combine like terms: 8x + -11x = -3x -3x = 3 + 11x + -11x Combine like terms: 11x + -11x = 0 -3x = 3 + 0 -3x = 3 Divide each side by '-3'. x = -1 Simplifying x = -1
| t+11=3(t-7) | | 11+4x=23 | | 7x+x=3x+6+5x | | 5n+3=-4 | | 18x=6x-35 | | 2(3x+1)=14-2x | | y=3x^2-30x+45 | | 5x-8+x=2(3x-8) | | -20=-4x-5x | | 42=4d-6d+6 | | 6y-7=2y+21-5y | | X-15=52 | | 4+9n+5=9 | | 2(2d+1)-3d=5(3d-2)+4d | | 2x^3=4x | | t^2+6t=-9 | | 5(2x+8)=-13+3 | | 0.3x-0.04(x+1)=3.04 | | 8(2n+5)=9(7n+3)+9 | | 8-3x=5x-10 | | -3(x-1)+9=10 | | 1-2(a+2)=9+a | | 20x+5y=1550 | | 27=-9(x+5) | | 7b+9=23 | | 18-c=11 | | 9x^2+12xy+4y^2= | | 9x=5x-12 | | -6-21=3p-12 | | 0.4(x+5)-0.3x=1 | | 3x-(x-3)=13 | | 8(x+7)=136 |